Impact of the Public-Private Partnership on the Socio-Economic Development: The Case of BMT (Bejaia Mediterranean Terminal) - Oukaci , Moustafa (Finance and Business Economies Review, 2023)
The aim of this research is to analyze the impact of a Public-Private Partnership (PPP) on socio-economic development, which combines the skills and resources of both sectors, thus sharing risks and responsibilities. We studied the case of the BMT (Bejaia Mediterranean Terminal) joint venture, a partnership between the Algerian public company PCB (Port Company of Bejaia) and the private Singaporean group Portek, which started in 2006. This partnership has allowed the improvement of the port activity and the implantation of an efficient system of container processing that meets international standards, through a transfer of knowledge and skills as well as an undeniable socio-economic impact on the region of Bejaia and on the national economy.